Building Capacity for Productive Indigenous Community-University Partnerships - Gittelsohn, Joel; Belcourt, Annie; Magarati, Maya; Booth-LaForce, Cathryn; Duran, Bonnie; Mishra, Shiraz I.; Belone, Lorenda; Jernigan, Valarie Blue Bird (Prevention science, 2020)
This paper describes capacity development as a key aspect of community-based research with indigenous communities. University research engagement with indigenous communities includes extensive, and often negative, historical antecedents. We discuss strategies for developing effective, egalitarian, and balanced indigenous community-university relationships to build research capacity of these communities, and to create sustainable partnerships to improve health and wellness, and to reduce health disparities. We draw on the experience of eight investigators conducting research with indigenous communities to assess effective strategies for building and enhancing partnerships, including (1) supporting indigenous investigator development; (2) developing university policies and practices sensitive and responsive to Indigenous community settings and resources, and training for research; (3) developing community and scientifically acceptable research designs and practices; (4) aligning indigenous community and university review boards to enhance community as well as individual protection (e.g., new human subjects training for Indigenous research, joint research oversight, adaptation of shorter consent forms, appropriate incentives, etc.); (5) determining appropriate forms of dissemination (i.e., Indian Health Services provider presentation, community reports, digital stories, etc.); (6) best practices for sharing credit; and (7) reducing systematic discrimination in promotion and tenure of indigenous investigators and allies working in indigenous communities.